Intracranial hemorrhage in hemorrhagic disease of the newborn - Irawan Mangunatmadja; Rina W Sundariningrum; Hardiono D Pusponegoro; Endang Windiastuti (Indonesian Pediatric Society Publishing House, 2016)
Background Hemorrhagic disease of the newborn (HDN) repre- sents a special case of vitamin K deficiency because the four vita- min K-coagulation factors (factors II,VII,IX,X) are already at physi- ologically low levels in the newborn. It responds to vitamin K therapy. Objective The aim of this study was to review the incidence, clini- cal manifestation, and outcome of HDN. Methods This was a retrospective cross sectional study on 22 patients hospitalized for HDN in the Department of Child Health, Cipto Mangunkusumo Hospital from January 1997 until Decem- ber 2001. Data were obtained from medical records. Results The commonest age group (17 out of 22) was 1-3 month- old. Normal delivery was found in 19 patients and only 3 patients received prophylaxis vitamin K. Almost all of them (20 out of 22) were exclusively breastfed. Seizure, pallor, decreased conscious- ness, and bulging of the anterior fontanel were significant clinical manifestations found in 21, 21, 13, and 9 patients respectively. Based on brain USG and/or CT scan, intracranial hemorrhage was found in 19 patients. Six out of 22 patients died and 7 patients survived with handicap Conclusion Intracranial hemorrhage due to vitamin K mostly oc- curred at the age of 1 to 3 month-old. The commonest clinical mani- festations were seizure, pallor, decreased consciousness, and bulging of the anterior fontanel. Prevention by giving vitamin K rou- tinely to all newborn babies is recommended